(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The very concept of business sustainability includes the economic success of the company and its social responsibility, while simultaneously protecting human and natural resources. The basic purpose of organizations is high-quality, reliable, and comprehensive reporting, which contributes to improving transparency and better management. Businesses today are experiencing a transition from traditional accounting to sustainable accounting. Sustainable accounting is the practice of measuring, analyzing, and reporting a company’s social, environmental, and governance impacts. Today businesses need accountants trained to accurately and comprehensively measure sustainability. To research and review novelties in the field of sustainable accounting numerous world literature has been researched. In this research, papers within the Scopus databases were used to gather information on the research topic which shows that a large number of authors have researched the area of sustainable development. Still, there is insufficient correlation and connection between sustainable accounting and sustainable development. A search of Scopus using the following approach (TITLE-ABS-KEY ("sustainable accounting") AND TITLE-ABS-KEY ("sustainable development") resulted in 47 scientific papers. From the aspect of sustainable development, it is essential to measure and report information regarding sustainability through sustainable accounting.